2017
DOI: 10.3390/polym9100538
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Polymerization of Styrene and 1,3-Butadiene in the Presence of Phosphazene Superbases

Abstract: Abstract:The anionic polymerization of styrene and 1,3-butadiene in the presence of phosphazene bases (t-BuP 4 , t-BuP 2 and t-BuP 1 ), in benzene at room temperature, was studied. When t-BuP 1 was used, the polymerization proceeded in a controlled manner, whereas the obtained homopolymers exhibited the desired molecular weights and narrow polydispersity (Ð < 1.05). In the case of t-BuP 2 , homopolymers with higher than the theoretical molecular weights and relatively low polydispersity were obtained. On the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…It has been shown that the rate of polymerization of styrene, initiated by carbanions, is accelerated in the presence of Lewis bases, such us ethers and amines . In our previous report, the anionic polymerization of styrene, in benzene at room temperature (23 °C), with sec ‐BuLi in the presence of superbases ( t ‐BuP 4 , t ‐BuP 2 , and t ‐BuP 1 ) with phosphazene /sec ‐BuLi: 0.5 (t ‐BuP 2 and t ‐BuP 1 ) and 1 ( t ‐BuP 4 , t ‐BuP 2 , and t ‐BuP 1 ) ratios, was studied . In the case of t ‐BuP 2 and t ‐BuP 1 , the results were comparable to the ones already published for Lewis bases .…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the rate of polymerization of styrene, initiated by carbanions, is accelerated in the presence of Lewis bases, such us ethers and amines . In our previous report, the anionic polymerization of styrene, in benzene at room temperature (23 °C), with sec ‐BuLi in the presence of superbases ( t ‐BuP 4 , t ‐BuP 2 , and t ‐BuP 1 ) with phosphazene /sec ‐BuLi: 0.5 (t ‐BuP 2 and t ‐BuP 1 ) and 1 ( t ‐BuP 4 , t ‐BuP 2 , and t ‐BuP 1 ) ratios, was studied . In the case of t ‐BuP 2 and t ‐BuP 1 , the results were comparable to the ones already published for Lewis bases .…”
Section: Resultsmentioning
confidence: 99%
“…PS- b -PEO number-average molecular weight ( M n ) = 80- b -30 (110 kDa) and PS- b -PEO M n = 58- b -22 (80 kDa) were synthesized by anionic polymerization via high-vacuum living anionic polymerization of styrene in benzene using sec -BuLi as the initiator at RT for 6 h followed by polymerization of ethylene oxide in the presence of t- BuP 4 at 45 °C for 48 h. , All other polymers used in this study, PS- b -PEO M n = 102- b -34 (136 kDa), PS- b -PEO M n = 480- b -227 (707 kDa), polystyrene- block -poly­(2-vinylpyridine) (PS- b -P2VP) M n = 79- b -36 (115 kDa), PS M n = 35 kDa, PS M n = 113 kDa, and PS M n = 173 kDa, were purchased from Polymer Source Inc. and used as received. All solvents and additives were purchased from Sigma-Aldrich and used as received.…”
Section: Methodsmentioning
confidence: 99%
“…Materials. PS-b-PEO number-average molecular weight (M n ) = 80-b-30 (110 kDa) and PS-b-PEO M n = 58-b-22 (80 kDa) were synthesized by anionic polymerization via high-vacuum living anionic polymerization of styrene in benzene using sec-BuLi as the initiator at RT for 6 h followed by polymerization of ethylene oxide in the presence of t-BuP 4 at 45 °C for 48 h. 30,31 and used as received. All solvents and additives were purchased from Sigma-Aldrich and used as received.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…In this method, the anionic active chain ends are actively maintained to permit the polymerization. There is a wide variety of monomers such as cyclic siloxanes, dienes, epoxides, styrenes, episulfides, and styrenes that can be polymerized anionically [Quirk, 2002;Ntetsikas et al, 2017]. Polystyrene and polydienes are typical examples of controlled block copolymer, that are synthesized by anionic polymerization.…”
Section: Ionic Polymerizationmentioning
confidence: 99%